Pengaruh Model Pembelajaran Kooperatif Tipe Course Review Horay terhadap Kemampuan Mengidentifikasi Perwatakan Drama Ayahku Pulang Karya Usmar Ismail Siswa Kelas VIII SMPN 1 Bojong Tahun Pelajaran 2018/2019 - Sauri, Sopyan; Haerunisa, Nadya (Universitas Mathla'ul Anwar Banten, 2019)
This study aims to find out the effect of the Course Review Horay type of cooperative learning model on the ability to identify my father's drama character back home by Usmar Ismail. This study uses an experimental method with a population of all eighth grade students of State Middle School 1 Bojong 2018/2019 academic year. The sampling technique used was cluster random sampling or random sampling. So that the random sampling technique obtained samples, namely class VIII D and class VIII E. Each of them amounted to 33 students, so that the overall sample amounted to 66 students. Class VIII D as the experimental class was given treatment in the form of using the Course Review Horay cooperative learning model, while class VIII E as the control class used the Teams Games Tournament learning model.Based on the results of data processing, it was obtained an illustration that the ability to identify my father's drama drama returned home by usmar ismail students using the Cooperative Course Review Horay type model well. This can be seen from 33 students who were obtained as many as 21 students or 63.63% obtaining scores more than 54. While 12 students or 36.36% scored between 38-53, the average score was 58.21; the highest score is 85 and the lowest value is 38. While the ability to identify drama officers with the cooperative learning model of the Teams Games Tournament type is not good. Drawing from 33 students studied, 21 students or 63.63% obtained grades less than 50. While 12 students or 36.36% scored between 51-70 with an average score of 47.63, the lowest score was 30, the highest score was 70. Thus, it can be concluded that there is a positive influence on the use of the Cooperative Course Review Horay type model on the ability to identify drama characters of my Ayah Pulang by Usmar Ismail, a grade VIII student at SMP 1 Bojong in the academic year 2018/2019.